Korelasi Tingkat Religiusitas Siswa dan Prokrastinasi Akademik di MBS Al Mukhtar Watukebo - Nirmalasari, Intan; Rofi, Sofyan; Huda, Hairul (Indonesian Journal Publisher, 2024)
Students, as academic actors, have a responsibility to fulfill their academic obligations, which include learning and completing academic tasks. The process of fulfilling these obligations and working on academic tasks requires consistency, understanding of priorities, and effective time management. If students are not aware of their responsibilities and lack these three elements, it can lead to the phenomenon of academic procrastination or delaying the completion of tasks. Therefore, it is necessary to have values that can serve as self-control and foster a sense of responsibility. The values that are believed to act as control mechanisms for students against the phenomenon of academic procrastination are religious and spiritual values. Hence, the researcher attempts to investigate the relationship between religious values and academic procrastination. The aim is for religious values to reduce students' academic procrastination. This study employs a quantitative research approach. The research intends to determine the correlation between students' religiosity levels and academic procrastination at MBS Al Mukhtar Watukebo in the even semester of 2022/2023. The research subjects consist of 58 students from MBS Al Mukhtar who were selected as research samples using a random sampling technique. Data was collected using questionnaires distributed to the 58 students as respondents. The research analysis employs the Pearson product-moment correlation test. The research findings indicate that students' levels of religiosity have a negative correlation with academic procrastination, as evidenced by a coefficient value greater than the critical value (r > r table). Therefore, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. This implies that there is a correlation between students' religiosity and academic procrastination at MBS Al Mukhtar Watukebo.